UTAUT Determinants of E-Commerce Hotel Booking Behavior at The ZHM Premiere Hotel Padang - Reza Amelia; Feri Ferdian (Pt. Threeple Herphi Educate, 2026)
This study examines the determinants of self-reported e-commerce hotel booking behavior at The ZHM Premiere Hotel Padang. Platform-based room reservations fluctuated between August 2022 and January 2023, indicating that channel availability alone did not ensure stable digital booking activity. A quantitative cross-sectional survey was conducted among 273 guests who had used an e-commerce platform to reserve a room at the hotel. The model applied four determinants from the Unified Theory of Acceptance and Use of Technology (UTAUT): performance expectancy, effort expectancy, social influence, and facilitating conditions. Use behavior was measured through questionnaire responses and therefore represents guests' self-reported booking use rather than transaction-log behavior. Data were analyzed with SPSS 26 and PLS-SEM in SmartPLS 3. The measurement model demonstrated acceptable reliability, convergent validity, and Fornell-Larcker discriminant validity. The structural model explained 61.1% of the variance in use behavior. Performance expectancy (beta = 0.372, p = 0.008) and effort expectancy (beta = 0.362, p = 0.007) were the strongest predictors, followed by social influence (beta = 0.154, p = 0.035) and facilitating conditions (beta = 0.098, p = 0.045). The findings indicate that hotel managers should prioritize practical booking value and simplicity, while maintaining social credibility and adequate transaction support.